Ijarah Muntahia Bittamlik: Comprehensive Analysis and Implementation in Sharia Financial Business in Indonesia - Azizah, Nur; Wahyuddin, Wahyuddin; Bulutoding, Lince (Invoice : Jurnal Ilmu Akuntansi, 2025)
Ijarah Muntahia Bittamlik (IMBT) is a Sharia-based financial instrument that merges the concept of leasing (ijarah) with a transfer of ownership, offering an innovative solution for long-term asset financing. This study aims to comprehensively analyze IMBT, comparing it with conventional leasing (ijarah) and evaluating its application in Indonesia's Islamic financial sector. A qualitative method with a descriptive-analytical approach was employed, drawing on literature reviews and industry data. The findings show that IMBT offers greater flexibility compared to conventional ijarah, especially in asset ownership transfer. In Indonesia, various Islamic financial institutions have implemented IMBT, but its growth faces challenges such as regulatory limitations, standardization of contracts, and low public awareness. The study emphasizes the need for enhanced regulation and greater efforts in public education to facilitate wider adoption. It also highlights the significant role of IMBT in addressing the increasing demand for Sharia-compliant asset financing, such as property and vehicle purchases. By providing practical recommendations, this study contributes to the development of IMBT literature and supports stakeholders in the Islamic financial industry to better utilize this financial product. IMBT's potential for growth in Indonesia is significant, especially in light of the expanding Islamic finance sector and increasing demand for asset financing solutions that align with Sharia principles.